2022
DOI: 10.3389/fbioe.2022.830189
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles From Microalgae: Uptake Studies in Human Cells and Caenorhabditis elegans

Abstract: Extracellular vesicles (EVs) are lipid membrane nano-sized vesicles secreted by various cell types for intercellular communication, found in all kingdoms of life. Nanoalgosomes are a subtype of EVs derived from microalgae with a sustainable biotechnological potential. To explore the uptake, distribution and persistence of nanoalgosomes in cells and living organisms, we separated them from a culture of the chlorophyte Tetraselmis chuii cells by tangential flow filtration (TFF), labelled them with different lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…Strains used in this work have been provided by the Caenorhabditis Genetics Center (CGC), which is funded by the NIH Office of Research Infrastructure Programs (P40 OD010440): wild-type strain N2, Bristol variety; CL2166 dvIs19 [(pAF15) pgst-4 :GFP:NLS] that expresses an oxidative stress-responsive GFP. Animal treatments with SPIONs@SiO 2 -PDA and Milli-Q water as mock were performed in iquid in 96-multiwell plates for the entire life-cycle of the animals (chronic treatment) . Synchronized eggs, obtained by bleaching, were resuspended in M9 buffer (3 g KH 2 PO 4 ; 6 g Na 2 HPO 4 ; 5 g NaCl; 1 M mgSO 4 ; H 2 O to 1 L) with 2× antibiotic/antimycotic solution (Sigma-Aldrich, A5955), 5 ng/mL cholesterol and OP50.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains used in this work have been provided by the Caenorhabditis Genetics Center (CGC), which is funded by the NIH Office of Research Infrastructure Programs (P40 OD010440): wild-type strain N2, Bristol variety; CL2166 dvIs19 [(pAF15) pgst-4 :GFP:NLS] that expresses an oxidative stress-responsive GFP. Animal treatments with SPIONs@SiO 2 -PDA and Milli-Q water as mock were performed in iquid in 96-multiwell plates for the entire life-cycle of the animals (chronic treatment) . Synchronized eggs, obtained by bleaching, were resuspended in M9 buffer (3 g KH 2 PO 4 ; 6 g Na 2 HPO 4 ; 5 g NaCl; 1 M mgSO 4 ; H 2 O to 1 L) with 2× antibiotic/antimycotic solution (Sigma-Aldrich, A5955), 5 ng/mL cholesterol and OP50.…”
Section: Methodsmentioning
confidence: 99%
“…Animal treatments with SPIONs@SiO 2 -PDA and Milli-Q water as mock were performed in iquid in 96-multiwell plates for the entire lifecycle of the animals (chronic treatment). 36 Synchronized eggs, obtained by bleaching, were resuspended in M9 buffer (3 g KH 2 PO 4 ; 6 g Na 2 HPO 4 ; 5 g NaCl; 1 M mgSO 4 ; H 2 O to 1 L) with 2× antibiotic/antimycotic solution (Sigma-Aldrich, A5955), 5 ng/mL cholesterol and OP50. 60 μL containing ∼30 eggs were aliquoted in each well.…”
Section: Acs Biomaterialsmentioning
confidence: 99%
“…Our previous study on nanoalgosomes showed that they are highly stable in human blood plasma, non-cytotoxic in vitro and can be taken up by various cellular systems 15,24 . Here, to fully characterize the compatibility, distribution, and bioactivity of nanoalgosomes, we conducted a comprehensive analysis both in vivo, using Caenorhabditis elegans and mice, in vitro with human cell lines, and ex vivo with human basophils from whole blood.…”
Section: Production and Quality Checking Of Nanoalgosome Preparationsmentioning
confidence: 99%
“…After quality checks on the nanoalgosome batches (Figure 1), we treated wild-type animals through in liquido culturing for 72 hours with increasing concentrations of nanoalgosomes (1,20,64, 128 µg/mL), first evaluating animal viability and capability of reaching adulthood. These concentrations were chosen because we had previously demonstrated that nanoalgosomes are successfully taken up by C. elegans at 20 µg/mL 24 .…”
Section: In Vivo Biocompatibility Of Nanoalgosomes In C Elegansmentioning
confidence: 99%
See 1 more Smart Citation